2001
DOI: 10.1111/j.1651-2227.2001.tb00794.x
|View full text |Cite
|
Sign up to set email alerts
|

Pre‐school children with developmental co‐ordination disorder: self‐perceived competence and group motor skill intervention

Abstract: Pless M, Carlsson M, Sundelin C, Persson K. Pre-school children with developmental coordination disorder: self-perceived competence and group motor skill intervention. Acta Paediatr 2001; 90: 532-538. Stockholm. ISSN 0803-5253 Objective: To investigate self-perceived competence in 5-to 6-y-old children with developmental co-ordination disorder. Subjects and methods: Scores in two scales of self-perceived competence were compared between a study group of children with developmental co-ordination disorder (n… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
52
0
3

Year Published

2005
2005
2017
2017

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(56 citation statements)
references
References 15 publications
0
52
0
3
Order By: Relevance
“…1991; Mæland 1992; Schoemaker & Kalverboer 1994; Christiansen 2000; Piek et al . 2000, 2005, 2007, 2008; Smyth & Anderson 2000; Pless et al . 2001; Skinner & Piek 2001; Dewey et al .…”
Section: Resultsmentioning
confidence: 99%
“…1991; Mæland 1992; Schoemaker & Kalverboer 1994; Christiansen 2000; Piek et al . 2000, 2005, 2007, 2008; Smyth & Anderson 2000; Pless et al . 2001; Skinner & Piek 2001; Dewey et al .…”
Section: Resultsmentioning
confidence: 99%
“…30 Similarly, a more recent study found that a 10-week intervention did not improve actual motor impairments, but did improve perceived self-efficacy toward specific tasks (eg, tying shoelaces) in children with DCD. 31 Therapists and others (parents and teachers) need to carefully consider a child's motor abilities, assist the child in finding a suitable vigorous activity and environment, and work incrementally toward improving the child's mastery of the task.…”
Section: Discussionmentioning
confidence: 99%
“…Based on the examination findings and the information found in the literature (e.g. Pless, Carlsson, Sundelin, and Persson, 2001;Polatajko et al, 1995), it would be reasonable to expect an initial program of intervention to cover at least 10 to 20 sessions.…”
Section: Diagnosis and Prognosismentioning
confidence: 99%